Primer Choice and Xylem-Microbiome-Extraction Method Are Important Determinants in Assessing Xylem Bacterial Community in Olive Trees - Manuel Anguita-Maeso; Carmen Haro; Juan A. Navas-Cortés; Blanca B. Landa (Plants, 2022)
Understanding the unique and unexplored microbial environment of xylem sap is starting to be of relevant importance for plant health, as it could include microbes that may protect plants against xylem-limited pathogens, such as Verticillium dahliae and Xylella fastidiosa. In this study, we evaluated the effects that the method for extracting the xylem bacterial communities, the plant age and the PCR primers may have on characterizing the xylem-bacterial-community composition by using an NGS approach. Xylem sap was extracted from xylem vessels by using a Scholander pressure chamber, or by macerating wood shavings that were obtained from xylem tissues by using branches from 10-year-old olive trees, or the entire canopy of 1-year-old olive plantlets. Additionally, we compared four different PCR-primer pairs that target 16S rRNA for their efficacy to avoid the coamplification of mitochondria and chloroplast 16S rRNA, as this represents an important drawback in metabarcoding studies. The highest amplifications in the mitochondria and chloroplast reads were obtained when using xylem woody chips with the PCR1-799F/1062R (76.05%) and PCR3-967F/1391R (99.96%) primer pairs. To the contrary, the PCR2-799F/1115R and PCR4-799F/1193R primer pairs showed the lowest mitochondria 16S rRNA amplification (<27.48%), no chloroplast sequences and the highest numbers of bacterial OTUs identified (i.e., 254 and 266, respectively). Interestingly, only 73 out of 172 and 46 out of 181 genera were shared between the xylem sap and woody chips after amplification with PCR2 or PCR4 primers, respectively, which indicates a strong bias of the bacterial-community description, depending on the primers used. Globally, the most abundant bacterial genera (>60% of reads) included Anoxybacillus, Cutibacterium, Pseudomonas, Spirosoma, Methylobacterium-Methylorubrum and Sphingomonas; however, their relative importance varied, depending on the matrix that was used for the DNA extraction and the primer pairs that were used, with the lowest effect due to plant age. These results will help to optimize the analysis of xylem-inhabiting bacteria, depending on whether whole xylematic tissue or xylem sap is used for the DNA extraction. More importantly, it will help to better understand the driving and modifying factors that shape the olive-xylem-bacterial-community composition.